Сучасні тренди та технології в цифровій технології - Слуцкін, М. В.; Вовк, О. В. (ХНУРЕ, 2025)
The text is devoted to the development of digital printing, which, thanks to technological innovations, is gradually replacing traditional printing methods. The main attention is paid to the advantages of digital printing: efficiency, flexibility, cost-effectiveness and the ability to personalize products. Considerable attention is paid to environmental approaches: recycled paper and waste-free production. In Ukraine, digital printing is actively used in marketing, in particular in personalized advertising materials. Further development of the industry is focused on automation, personalization and integration of the latest technologies. This will increase the efficiency of printing houses and ensure stable product quality. Digital printing is becoming a key platform for innovation.
Keywords: digital printing; traditional printing methods